Effects of Zinc Administration on Mood and Psychotic Disorders: A Literature Review - Benly Levi Andreas Sibarani; Shella Sharon; Aurora Fajria Anwari; Maeike Grestiana Sinaga (CV Projurnal Mitra Publikasi, 2025)
Zinc is one of the macronutrients associated with emotional, cognitive, and behavioral processes. Zinc deficiency is a serum zinc concentration < 70 μg/dl. Zinc deficiency is associated with neurosensory disorders, and is also closely associated with mood disorders such as depression. Mood disorders and psychosis consist of depression, bipolar disorder, and schizophrenia. Several existing studies suggest that nutritional factors, especially the role of micronutrients such as zinc, may contribute to the pathophysiology and management of mood and psychotic disorders. To determine the effect of zinc administration on mood disorders and psychosis. This study used a systematic literature review method using three main electronic databases including Pubmed, ScienceDirect, and Researchgate. From the results of the literature search, 11 clinical articles and studies were obtained, published from 2015 to 2025. Of the eleven articles used in the literature review, nine of them showed a significant relationship between zinc and mood and psychotic disorders. There is a positive relationship between zinc supplementation, serum zinc levels, and mood disorders and psychotics.